PERSEPSI GURU TERHADAP PENDIDIKAN SEKS BAGI SISWA DI MIS MUHAMMADIYAH 3 AL-FURQAN BANJARMASIN - Nur Amalia Husna; Siti Shalihah (Program Studi PGMI STAI Al Falah Banjarbaru, 2026)
Introducing sex education to elementary school students is often considered taboo, even though during this period, children begin to experience physical and emotional changes that are important for them to understand. In addition to parents, teachers also play a crucial role in introducing sex education in schools. Furthermore, early introduction of sex education is expected to reduce the rate of sexual abuse among children. The purpose of this study was to determine teachers' perceptions of sex education for students at MIS Muhammadiyah 3 Al Furqan Banjarmasin. The method used in this study was descriptive qualitative. The subjects were Fiqh (Islamic jurisprudence) and Science (science) teachers, and homeroom teachers. The object of this study was teachers' perceptions of sex education for students at MIS Muhammadiyah 3 Al Furqan Banjarmasin. Data collection techniques included observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and drawing conclusions. Triangulation was used to verify the validity of the data. The results showed that teachers had positive perceptions because they encompassed all components of attitudes: cognitive, affective, and conative. The strategies teachers use to introduce sex education at the elementary school level include choosing polite language, using simple language to avoid overly stimulating students' curiosity, and linking sex education to classroom learning materials such as Islamic jurisprudence (fiqh) and science. Challenges teachers face in delivering sex education in schools include difficulty choosing words and delivering material that must be tailored to the child's level of understanding and age, a lack of support from parents who consider sex education at the elementary school level taboo, and the challenge of linking sex education material to lessons without diminishing moral and religious values. Thus, sex education can be delivered effectively as a form of student protection and character development.